Do tratamento das Convenções Internacionais do Trabalho no Sistema Jurídico Brasileiro - Abreu, Fernanda de Miranda Santos Cezar de (2013)
This paper aims to study the international labor conventions arising from the International Labour Organization and the treatment they received in the Brazilian legal system. To do so, we start the study of the general theory of treaties, encompassing its species (including a novel kind of human rights treaties), its relationship with national law - including the hierarchy that will once internalized-, its ratification and its complaint always tangential to the vision of the Supreme Court on the respective subjects. Then move into the study of the International Labour Organization and what its creation represented to the consolidation of labor law and human rights, analyzing the instruments owned by this organization for the protection of these rights and their specific front treaties in general. Finally, we will analyze three ILO conventions: the n° 132, 87 and 158, because they represent different situations facing our constitutional system and allow an accurate analysis and practice of all institutes here scattered, allowing us to give an overview of treatment received by the international labor conventions by the highest court of the country and by the law enforcement in general. Because this is a descriptive study, it will be based on research, sometimes using the deductive method and other inductive, especially in critical reflections on the normative texts